2012
DOI: 10.1128/aem.07015-11
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Enumeration, Serotypes, and Antimicrobial Resistance Phenotypes of Salmonella enterica Isolates from Carcasses at Two Large United States Pork Processing Plants

Abstract: The objective of this study was to characterize Salmonella enterica contamination on carcasses in two large U.S. commercial pork processing plants. The carcasses were sampled at three points, before scalding (prescald), after dehairing/polishing but before evisceration (preevisceration), and after chilling (chilled final). The overall prevalences of Salmonella on carcasses at these three sampling points, prescald, preevisceration, and after chilling, were 91.2%, 19.1%, and 3.7%, respectively. At one of the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 58 publications
1
16
1
Order By: Relevance
“…The present study found S. London and S. Haifa serotypes, which are rather infrequent serotypes in pigs (25). A study performed in Uganda reported S. Newport, S. Guildford, S. Coleypark, S. Damman as frequent pig serotypes (26), previously described in humans.…”
Section: Resultssupporting
confidence: 69%
“…The present study found S. London and S. Haifa serotypes, which are rather infrequent serotypes in pigs (25). A study performed in Uganda reported S. Newport, S. Guildford, S. Coleypark, S. Damman as frequent pig serotypes (26), previously described in humans.…”
Section: Resultssupporting
confidence: 69%
“…However, scalding and singeing are known to decrease the prevalence of Salmonella on carcasses (Dickson and others ). Preevisceration carcasses were 19.1% positive with only 5% of samples containing enumerable levels of Salmonella which is greatly reduced compared to prescalded carcasses (Schmidt and others ). In addition to feces, various lymph nodes have also been documented as being a reservoir for Salmonella (Fosse and others ).…”
Section: Salmonellamentioning
confidence: 94%
“…Overall, the slaughter process decreases the prevalence of Salmonella on the carcass (Saide鈥怉lbornoz and others ; Dickson and others ). After final rinse and carcass chilling, prevalence of Salmonella was found to be 3.7% (Schmidt and others ).…”
Section: Salmonellamentioning
confidence: 98%
See 1 more Smart Citation
“…Rissen is a commonly reported serotype around the world and it is amongst the top three serotypes found in pigs and pork products in Europe and Southeast Asia [3]. Numerous studies have identified S. Rissen in slaughtered pigs in Portugal [4] and within pig fattening units and from slaughter-age pigs and Spain [5] [6] [7] [8] [9].…”
Section: Introductionmentioning
confidence: 99%